La utilización de la expresión plástica para mejorar el desarrollo de la motricidad fina de las niñas y niños de 4 a 5 años de la escuela de educación básica Filomena Rojas Ocampo de la ciudad de Loja, periodo 2014-2015 - Rivadeneira Saraguro, Oswaldo Xavier (2016)
The study, entitled: USE OF PLASTIC EXPRESSION TO IMPROVE THE DEVELOPMENT OF FINE MOTOR SKILLS OF CHILDREN 4 TO 5 YEARS BASIC EDUCATION SCHOOL OF FILOMENA ROJAS OCAMPO LOJA CITY, 2014-2015. It was formulated as general objective: to design teaching strategies of artistic expression for the development of fine motor skills of children from 4-5 years of the School of Basic Education Filomena Rojas Ocampo city of Loja, 2014-2015. The type of study was descriptive-correlational in which methods were used: analytical, analytic-synthetic, inductive, synthetic; likewise the techniques and instruments were the survey aimed at entry-level teachers, to establish the types of artistic expression they use in daily work with children and Test Dexterímetro Goddard, applied to infants Initial Level 2, to determine the development of fine motor skills. The study population consists of 21 children and 2 teachers initial level. We conclude that artistic expression is a resource of importance in the initial level, because it helps improve fine motor skills of children through the use of various techniques such as finger paint, wrinkled, cut and paste; and likewise the materials used were: crayons, paint and paper.